Legal Power of Testament Act as Authentic Deed in The Indonesian and Malaysian Law System - Izzah Afkarina (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2022)
The Testament is a letter that contains a person's statement about what they want on assets after they die. In principle, in civil matters in the Indonesian legal system (Civil Law), written evidence is prioritized evidenceor the highest evidence than others. In contrast to Malaysia (Common Law), in the law of proof, it uses a jury system. Legal issues are determined by the judge and the facts are determined by the jury. From the explanation above, the Testament deed doesn’t have to do because the heirs are entitled on the inheritance of the property. Based on the description above, it needs to further examine “The Comparison of the Testament Deed Law as an authentic deed of Law in the Legal System in Indonesia and Malaysia”. The method used in this research is Qualitative Method, using Normative Law research. The results showed that (1) The Testament Regulation in the legal system in Indonesia and Malaysia is still pluralism of law; (2) The legal force of the Testament Deed and the legal consequences are both perfect proof in the Court if it fits its the procedures and provisions; (3) The Implementation of Testament Deeds in the legal system of the Indonesian and Malaysia, both can be done in writing, verbally or signal and it is witnessed with two witnesses.